2007
DOI: 10.1111/j.1365-2265.2007.03115.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome (MS) in children and adolescents with varying degrees of obesity

Abstract: The prevalence of the MS is higher in obese as opposed to nonobese subjects and increases with severity of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
98
1
16

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 38 publications
9
98
1
16
Order By: Relevance
“…Obese patients have a three-fold increased risk of developing the MS with respect to overweight patients (21) . The present study found that the prevalence of the MS among female Kuwaiti adolescents was 14·8 and 9·1 %, according to the IDF and ATP III, respectively, which is high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese patients have a three-fold increased risk of developing the MS with respect to overweight patients (21) . The present study found that the prevalence of the MS among female Kuwaiti adolescents was 14·8 and 9·1 %, according to the IDF and ATP III, respectively, which is high.…”
Section: Discussionmentioning
confidence: 99%
“…In Kuwait, the overall prevalence of overweight and obesity has been found to be 30·9 and 13·9 %, respectively, among adolescents aged 10-14 years, which probably increased through the years due to the effects of modernisation, increased food consumption and sedentary lifestyles (2,3) . The prevalence of overweight and obesity was 28·6 and 7·9 %, respectively, among Qatari adolescents (4) , 21·5 and 13·7 % in United Arab Emirates (5) and in Saudi Arabia the prevalence of obesity ranged from 33·9 % in Ha'il to 11·7 % in Jizan.Overweight and obesity are associated with the metabolic syndrome (MS) (6) , even in children (7) . The MS has been shown to be associated with a variety of morbid conditions, chief among which are CVD or type 2 diabetes mellitus (T2DM) (8) ; it doubles the risk for CVD and further raises the risk for T2DM by about 5-fold (9) .…”
mentioning
confidence: 99%
“…Furthermore, the MS prevalence increases with the severity of obesity and reaches 50% in severely obese children (2). Increasing evidence suggests that numerous endocrine peptides, interleukins (IL), and cytokines, which are secreted mostly from adipose tissue, play a role in both short-and longterm energy balance, metabolism, and inflammatory response (3).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that children and adolescents who are obese are at greater risk for bone and joint problems, sleep apnoea, and social and psychological problems compared with their normal-weight peers (2)(3)(4) . Childhood obesity has also been found to be associated with cardiovascular risk factors such as hypertension, dyslipidaemias, diabetes and metabolic syndrome (5)(6)(7)(8) .…”
mentioning
confidence: 99%